Bacillus spp. metabolites are effective in eradicating Aedes aegypti (Diptera: Culicidae) larvae with low toxicity to non-target species - Falqueto, Silvia Altoe; Pitaluga, Bruno Faria; Sousa, Janaina Rosa de; Targanski, Sabrina Ketrin; Campos, Mateus Gandra; Oliveira Mendes, Tiago Antonio de; Silva, Gilvan Ferreira da; Siqueira Silva, Dulce Helena [UNESP]; Soares, Marcos Antonio (Elsevier B.V., 2021)
The growing spread of dengue, chikungunya and Zika viruses demand the development of new and environmentally safe control methods for their vector, the mosquito Aedes aegypti. This study aims to find novel larvicidal agents from mutualistic (endophytic and rhizospheric) or edaphic bacteria that have no action against nontarget organisms. Eleven out of the 254 bacterial strains tested were able to kill Ae. aegypti larvae. Larvicidal activity did not depend on presence of cells, since culture supernatants or crude lipopeptide extracts (CLEs) killed the larvae. Bacillus safensis BacI67 and Bacillus paranthracis C21 supernatants were the best performing supernatants, displaying the lowest lethal concentrations (LC50 = 31.11 mu L/mL and 45.84 mu L/mL, respectively). Bacillus velezensis B64a and Bacillus velezensis B15 produced the best performing CLEs (LC50 = 0.11 mg/mL and 0.12 mg/mL, respectively). Mass spectrometry analysis of CLEs detected a mixture of surfactins, iturins, and fengycins. The samples tested were weakly- or non-toxic to mammalian cells (RAW 264.7 macrophages and VERO cells) and non-target organisms (Caenorhabditis elegans, Galleria mellonella, Scenedesmus obliques, and Tetrahymena pyriformis) - especially B. velezensis B15 CLE. The biosynthetic gene clusters related to secondary metabolism identified by whole genome sequencing of the four best performing bacteria strains revealed clusters for bacteriocin, beta-lactone, lanthipeptide, non-ribosomal peptide synthetases, polyketide synthases (PKS), siderophores, T3PKS, type 1 PKS-like, terpenes, thiopeptides, and trans-AT-PKS. Purification of lipopeptides may clarify the mechanisms by which these extracts kill Ae. aegypti larvae.
Keywords: Bacillus safensis; Bacillus paranthracis; Bacillus velezensis; Lipopeptide; Genome mining